The Impact of Social Media Usage on Political Efficacy and Political Participation of Generations Y and Z in Thailand - Jinarat, Veerasak (Arts of Management Journal, 2024)
The utilization of social media usage for developing political efficacy and political participation in generations Y and Z is necessary and continuously developed to enhance voting activities. Consequently, the researcher collected a sample of 156 respondents, 18 – 41 years of age, in Thailand. The data was analyzed by multi-regression analysis. The results revealed that the components of social media usage, such as election, sharing, and comment, predicted significant political efficacy, at R2 = .23, .10, and .06, respectively, F = 36.535 (Sig .000). Moreover, the results also showed that internal political efficacy predicted significantly political participation at R2= .13 (Sig .000). Meanwhile, external political efficacy predicted significantly to political participation at R2 = .38 (Sig .00). These two components of political efficacy predicted simultaneously and significantly political participation at R2 = .24, accumulation error = .79, F = 247.46 (Sig .000). Consequently, the results contribute the approach for developing internal and external political efficacy to inspire directly the two generations in political participation.